OUTSOURCING AND TRUST TOWARDS USERS' SATISFACTION THROUGH THE COMPANY'S PERFORMANCES IN PUTRA MENTARI INCORPORATION - Finarsih, Eldining Wahyu; Setiawan, Margono; Salim, Ubud (Jurnal Aplikasi Manajemen, 2023)
This research was conducted on how the company's performance affected the company's satisfaction. The purpose of this study is to determine whether outsourcing and trust affect user company satisfaction through company performance as a mediation, whether it has a significant effect or not. The method used for this research was descriptive quantitative. The data were collected by spreading close questionnaires to Gracia Optima Incorporation Inc. and Bintang Prima Kemasindo Inc. as the clients of Putra Mentari Inc., an outsourcing company. In this study, PT Gracia Optima Masterpro and PT Bintang Prima Kemasindo are the populations, and samples were taken from 33 samples from both companies. This study used a saturated sampling technique using all the leaders and staff in both companies. The result showed that trust and good outsourcing given by Putra Mentari Inc. were the keys to getting the clients' satisfaction. It is hoped that the next research can break down the outsourcing variables and package them in more detail and specifically related to the work contract. Trust is one of the most influencing factors that outsourcing companies must maintain to keep the cooperation running for such a long period. It is also supported by good performance. This research could also function as a new insight into future research about the theories, trust, satisfaction, and performance in outsourcing practices.